Conformational dynamics in interleukin 17A and 17F functional complexes is a key determinant of receptor A affinity and specificity. (June 2021) - Waters, Lorna C.; Veverka, Vaclav; Strong, Sarah L.; Muskett, Frederick W.; Dedi, Neesha; Lawson, Alastair D.G.; Prosser, Christine E.; Taylor, Richard J.; Henry, Alistair J.; Carr, Mark D.
Graphical abstract: Highlights: NMR studies of the IL-17 family are consistent with reported crystal structures. Receptor binding sites in IL-17AA are characterised by conformational plasticity. Strikingly less conformational dynamics is observed in IL-17AF and IL-17FF. Structural plasticity governs the affinity of the IL-17 family for receptor A. Conformational dynamics is unlikely to influence IL-17 affinity for receptor C. Abstract: The proinflammatory cytokines IL-17A and IL-17F have been identified as key drivers of a range of human inflammatory diseases, such as psoriasis, which has led to several therapeutic antibodies targeted at IL-17A. The two cytokines have been shown to tightly associate as functional homo and hetero dimers, which induce signalling via the formation of a cell surface signalling complex with a single copy of both IL-17RA and IL-17RC. Striking differences in affinity have been observed for IL-17RA binding to IL-17AA, IL-17AF and IL-17FF, however, the functional significance and molecular basis for this has remained unclear. We have obtained comprehensive backbone NMR assignments for full length IL-17AA (79%), IL-17AF (93%) and IL-17FF (89%), which show that the dimers adopt almost identical backbone topologies in solution to those observed in reported crystal structures. Analysis of the line widths and intensities of assigned backbone amide NMR signals has revealed striking differences in the conformational plasticity and dynamics of IL-17AA compared to both IL-17AF and IL-17FF. Our NMR data indicate that a number of regions of IL-17AA are interconverting between at least two distinct conformations on a relatively slow timescale. Such conformational heterogeneity has previously been shown to play an important role in the formation of many high affinity protein-protein complexes. The locations of the affected IL-17AA residues essentially coincides with the regions of both IL-17A and IL-17F previously shown to undergo significant structural changes on binding to IL-17RA. Substantially less conformational exchange was revealed by the NMR data for IL-17FF and IL-17AF. We propose that the markedly different conformational dynamic properties of the distinct functional IL-17 dimers plays a key role in determining their affinities for IL-17RA, with the more dynamic and plastic nature of IL-17AA contributing to the significantly tighter affinity observed for binding to IL-17RA. In contrast, the dynamic properties are expected to have little influence on the affinity of IL-17 dimers for IL-17RC, which has recently been shown to induce only small structural changes in IL-17FF upon binding.